When ‘Perma’ Is No Longer ‘Perma’: Investigating Permafrost Degradation in Churchill, Manitoba - Street, Emma (2020)
This major paper explores the physical, economic, and cultural consequences of thawing permafrost in Churchill, Manitoba. By analysing a combination of texts and permafrost data, this paper examines how permafrost degradation will reshape Churchill’s make up in future years. The research questions I address are as follows: (1) To what extent is permafrost thawing in Churchill, Manitoba? (2) What are the implications of thawing permafrost in Churchill, Manitoba? Specifically: (a) How does thawing permafrost affect economic activity (primarily ecotourism) in Churchill? (b) In what ways does thawing permafrost affect the cultural practices of Churchill’s Indigenous population (Chipewyan, Swampy Cree, Métis, Dene, and Inuit)? Finding suggests that at least a quarter of Churchill’s continuous permafrost will degrade in the next fifty years and may completely disappear by the end of the century (Gagnon & Gough, 2005; Gough & Leung, 2002). The extent of this thaw creates a positive feedback loop with Churchill’s industries, further threatening the sustainability of the town’s activities and ground stability. This paper concludes with recommendations for future research on how to move forward as a town in transition.